STUDENT’S INSIGHT INTO THE USE OF E-PORTFOLIOS FOR A REFLECTIVE PRACTICE PROJECT - Yashilfa Dwi Chandra Rani; Nissa, Khairun (Esteem Journal of English Education Study Programme, 2025)
In the digital age, the integration of technology in education has transformed how students submit assignments, with e-portfolios emerging as a dynamic platform. E-portfolios offer students a personalized digital space to document their learning progress, showcase achievements, and engage in reflective practice. This study explores the perceptions of English student teachers regarding the use of e-portfolios in a reflective practice project. Utilizing a qualitative approach, both questionnaires and interview data were collected with 14 students. The findings reveal that students perceive e-portfolios as beneficial for tracking their growth, visualizing progress, and supporting reflective learning. Despite these benefits, challenges such as technical difficulties and time constraints were also noted. The study highlights the significance of e-portfolios as an alternative assessment tool and emphasizes their role in enhancing self-reflection and professional growth. However, addressing technical issues and time management is crucial for maximizing the potential of e-portfolios in education.